2022
DOI: 10.1002/smll.202205572
|View full text |Cite
|
Sign up to set email alerts
|

End‐Group Engineering of Chlorine‐Trialkylsiylthienyl Chain‐Substituted Small‐Molecule Donors for High‐Efficiency Ternary Solar Cells

Abstract: Ternary architecture has been widely demonstrated as a facile and efficient strategy to boost the performance of organic solar cells (OSCs). However, the rational design of the third component with suitable core and end‐group modification is still a challenge. Herein, two new small‐molecule (SM) donors BT‐CN and BT‐ER, featuring the identical conjugated backbone with distinct end group, have been designed, synthesized, and introduced into the PM6:Y6 binary system as the second donor. Both molecules exhibit com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…In the heating process, BZ4F-O-1 and BZO-4Cl exhibit their endothermic peaks at 240.4 o C and 215.9 o C, respectively. The BZ4F-O-1: BZO-4Cl (1: 1, w/w) mixture shows a medium value of melting temperature at 223.4 o C, while the melting peaks of neat BZ4F-O-1 and BZO-4Cl are disappeared, suggesting good miscibility between BZ4F-O-1 and BZO-4Cl [51] . Atomic force microscopy (AFM) is employed to investigate the surface morphology of the devices based on PBDB-T: BZ4F-O-1, PBDB-T: BZO-4Cl and PBDB-T: BZ4F-O-1: BZO-4Cl blends.…”
Section: Resultsmentioning
confidence: 98%
“…In the heating process, BZ4F-O-1 and BZO-4Cl exhibit their endothermic peaks at 240.4 o C and 215.9 o C, respectively. The BZ4F-O-1: BZO-4Cl (1: 1, w/w) mixture shows a medium value of melting temperature at 223.4 o C, while the melting peaks of neat BZ4F-O-1 and BZO-4Cl are disappeared, suggesting good miscibility between BZ4F-O-1 and BZO-4Cl [51] . Atomic force microscopy (AFM) is employed to investigate the surface morphology of the devices based on PBDB-T: BZ4F-O-1, PBDB-T: BZO-4Cl and PBDB-T: BZ4F-O-1: BZO-4Cl blends.…”
Section: Resultsmentioning
confidence: 98%
“…[25,26] Moreover, 2D conjugated molecules are more inclined to form a face-on stacking orientation, enabling efficient hole extraction and transport in solar cells. [27][28][29] However, the 2D conjugate engineering strategy is largely unexplored in D-A structure small molecule HTMs. [30,31] Herein, for the first time, triphenylamine (TPA) groups were incorporated as side chains of BDT unit to extend the longitudinal conjugate, achieving two 2D small molecule HTMs (XF2 and XF3) with longitudinal conjugate extension (Figure 1).…”
Section: (2 Of 10)mentioning
confidence: 99%
“…[ 25,26 ] Moreover, 2D conjugated molecules are more inclined to form a face‐on stacking orientation, enabling efficient hole extraction and transport in solar cells. [ 27–29 ] However, the 2D conjugate engineering strategy is largely unexplored in D–A structure small molecule HTMs. [ 30,31 ]…”
Section: Introductionmentioning
confidence: 99%
“…[46] In our previous study, we reported different end-group-based SM donors and the resulting ternary OSCs reached a PCE of 18.11%. [47] Besides, we modified the BDT unit by introducing a phenyl-substituted side chain, to regulate the energy level and crystallinity of the material. The ternary OSCs achieved PCE of 18.41%.…”
Section: Introductionmentioning
confidence: 99%